2013
DOI: 10.1021/jp4014866
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the Effects of Bend-Excitation in the F + CD4(vb=0,1) → DF(v) + CD3(v2=1,2) Reactions

Abstract: The title reaction was studied over the collisional energy range 0.9-4.0 kcal mol(-1), using a time-sliced velocity-imaging technique in a crossed-beam experiment. Both the integral and differential cross sections were measured in a product pair-correlation manner. Experimental evidence for the dual reaction mechanisms, a direct abstraction and a resonance-mediated pathway, were presented and await future theoretical confirmation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 62 publications
(141 reference statements)
2
19
0
Order By: Relevance
“…The effects of exciting various vibrational modes of the methane reactant have been examined by Liu and coworkers. [51][52][53][54] Interestingly, the excitation of the C-H stretching (v 1 ) mode in CHD 3 was found at low collision energies to inhibit its reaction with F, leading to the HF + CD 3 products. 51 This surprising effect was speculated as the result of the stereodynamical forces exerting on the approaching reactants by the pre-reaction van der Waals wells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of exciting various vibrational modes of the methane reactant have been examined by Liu and coworkers. [51][52][53][54] Interestingly, the excitation of the C-H stretching (v 1 ) mode in CHD 3 was found at low collision energies to inhibit its reaction with F, leading to the HF + CD 3 products. 51 This surprising effect was speculated as the result of the stereodynamical forces exerting on the approaching reactants by the pre-reaction van der Waals wells.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, both experimental and QCT results suggested that the bending excitation enhances the reaction at low collision energies, but inhibits the reaction at high collision energies. [53][54]56 However, it was argued that the reaction is mediated by resonances at this energy range.…”
Section: Resultsmentioning
confidence: 99%
“…Obviously, it cannot account for the collisional energy dependency of the reactant mode (vibration vs. translation) preference and the translational propensity almost universally found at lower E c . 21,25,27,76,77,84,85 Then, is the vibrational-induced steric effect relevant to Polanyi's rules and the mode-/bond-selectivity? The energy requirement in Polanyi's rules deciphers the relative efficacies of different forms of reactants' energy (vibration or translation) to surmount the reaction barrier.…”
Section: Concluding Remarks and Outlookmentioning
confidence: 99%
“…In literature it can be observed that many adsorption isotherms, applied for various systems, were tested on MIP systems also. Langmuir, bi‐Langmuir, tri‐Langmuir, Freundlich, Freundlich‐Langmuir, Dubinin‐Radushkevic, Temkin, Halsey, Jovanovic, bi‐Jovanovic, Freundlich‐Jovanovic, and Harkins‐Jura isotherms were used to express the adsorption in MIPs , while Lagergren first order, pseudo second order, and Elovich models were used to evaluate the kinetics in these selective adsorbents .…”
Section: Introductionmentioning
confidence: 99%